Career and Self-Construction of Emerging Adults: The Value of Life Designing - Maree, Jacobus G.; Twigge, Adeline (Frontiers in Psychology, 2016)
This article describes a potential way of counselling emerging adults from a life design perspective to construct a self that could enable them to be agents of both their own development and the development of others. Theoretical issues relating to a dynamic, developmental and systems framework of the understanding of wellbeing are described and the process involved is delineated. The research design was qualitative and comprised case studies. Six participants who subscribed to the definition of ‘emerging adults’ and were comparatively representative of the ethnic diversity of South Africa, were selected purposively from a group of individuals who applied for career counselling in a private practice context. The intervention involved life design counselling and occurred over a period of six weeks. Information related to participants’ self-construction was gathered using qualitative techniques, including the Career Interest Profile, the Career Construction Interview, a timeline, video clips, a collage, and semi-structured interviews. Following the intervention, the participants revealed heightened insights with regard to aspects of their sense of a relational-moral self. Results indicated that life design counselling could enhance elaborative personal development (enhancing self-awareness and reaping the benefits of developing an improved relational-moral self) and the promotion of an awareness of the importance to promote social justice in work-related contexts.